Integrated Ultrasonic Driven Balancer for Ultra Precision High Speed Machine Tools. (2016) - Foremny, Eike; Schenck, Christian; Kuhfuss, Bernd
Abstract: Ultra precision machining -in particular milling and drilling- is a flexible way to produce parts with optical surface quality. Due to the tight tolerances of the process parameters, air bearing spindles are necessary for ultra precision machining. The low axial and radial stiffness of the air bearing spindle requires a much better balance state than the ISO balancing grade G1 that is applied to conventional spindles in order to avoid damage to the air bearings. State of the art balancing of an ultra precision spindle is manu- ally done and hence a time consuming and error prone procedure. Due to the human interaction and uncertainties in the unbalance detection multiple iterations are necessary in order to achieve a sufficient balancing state. In this paper a experimental setup that evaluates the capability of an autonomous, in-spindle balancing system based on angular redistribution of masses is presented. The necessary angular torque to change the angle of the balancing mass is provided by a ring-shaped ultrasonic traveling wave motor. The properties of this system are investigated in regards to the smallest possible step of the drive. Particular attention is paid to the influence of different drive parameter values on the behavior of the ultrasonic motor. It is shown that the balance mass can be rotationally shifted with a resolution better than 0.05°, -fully adequate for ultra precision balancing.